The history of science through the prism of race - Elise K. Burton; Sayori Ghoshal; James Poskett (BJHS Themes)
One methodological approach to grasping a ‘big-picture’ history of modern science involves tracing the complex entanglements between scientific knowledge and the development of racism and racialized economic systems. Indeed, no historical account of any scientific field can be complete without acknowledging the role of race as an intellectual, social or economic factor. We substantiate this argument through a synthetic review of three overlapping threads in the historiography of science. First, historical research on ‘race science’ has analysed the formation of disciplines directly involved in constructing scientific concepts of race, including medicine, anthropology, linguistics, phrenology, psychology, archaeology and genetics. Second, historians have demonstrated that connections between race and science are not limited to the domain of race science. Rather, European imperial expansion, colonialism and capitalism created the foundational infrastructures undergirding the emergence of modern professional science. Finally, new research shows how race remains covertly embedded in theoretical frameworks, statistical formulae and technological devices still used by scientists today. Through these examples, we perceive a big-picture history of science in which its co-constitution with race links localized case studies and imperial narratives across space and time.